Expertise of the Economic Efficiency in Land Transport - Maciej GLINIAK; Sławomir KURPASKA; Krzysztof GÓRKA; Paweł BARAN (Communications of International Proceedings, 2021)
Strong competition in transport services prompts companies to constantly optimize costs. Therefore, the management and operation of vehicles becomes very important. The aim of the study was to provide an expert opinion of costs related to fuel consumption in a medium-sized transport company. This paper presents the aspect of fuel consumption and information related to the proper use of vehicles. The analysis was made on the basis of information obtained from the company. The specifications of the company's machinery and the annual use of vehicles are presented. This paper analyzes the energy efficiency of road transport and the costs related to fuel use. On the basis of the obtained results, the current economic situation of the company was presented and tips for improving the economic efficiency were suggested.
Keywords: transport; exploitation; efficiency; fuel; transport costs